Chronic Dacryocystitis and Success Rate of External Dacryocystorhinostomy in Makarak Hospital - Thaitanundr, Anukul (Journal of Health Science of Thailand, 2017)
The objective of this retrospective descriptive study was to study the epidemiology of chronic dacryocystitis from primary acquired nasolacrimal duct obstruction and success rate of external dacryocystorhinostomy (DCR) in Makarak Hospital. It reviewed 35 patients medical records with chronic dacryocystitis due to primary acquired nasolacrimal duct obstruction who were treated by external dacryocystorhinostomy without bicanalicular silastic tube intubation. It was found that patients were predominantly menopausal females (33 patients : 94.28%). Success rate was 94.28 percent after external dacryocystorhinostomy without bicanalicular silastic tube intubation and considered an effective method.